(untitled) (Czech Journal of International Relations, 2009)
Marion Demossier (ed.): The European Puzzle: The Political Structuring of Cultural Identities at a Time of Transition. 1st ed. New York: Berghahn Books, 2007, 220 stran, ISBN 978-1-57181-626-9.